A Patients' Perspective Towards the Injection Devices for Humira® and Imraldi® in a Nationwide Switching Program - Karlsdottir, Kristin; Gunnarsdottir, Anna I.; Grondal, Gerdur; Love, Thorvardur J.; Stefansdottir, Elinborg; Davidsdottir, Loa G.; Thorleifsdottir, Ragna H.; Gudbjornsson, Bjorn (Frontiers in Medicine, 2022)
Objective: Due to a tender process in Iceland, all patients on Humira were switched nationwide to its biosimilar Imraldi in March 2019. The study aimed to explore the patient’s perspective of the Humira and Imraldi injection devices. Methods: A standard telephone interview was carried out among patients with inflammatory arthritis, inflammatory bowel disease and psoriasis, who underwent this nationwide switching program a few months earlier. Results: The response rate was 84.5% (n=198). The average age was 50.8 years, and 53.5% were female. The patients self-administered the drugs in 96% of the cases. The majority (90.5%) stated that they received individualized instruction on using the Humira pen, compared to 18.2% who accepted instruction in the case of the Imraldi pen. Almost half (46.6%) of the patients found it more difficult to use the Imraldi pen than the Humira pen, while only 12.5% found the Imraldi pen easier to use. Firstly, these differences were due to more painful insertion of the needle (62.2%) and secondly, due to the experience, the injection process was different (63.0%). Conclusion: Patients with inflammatory disorders who have been treated regularly with adalimumab preferred the Humira injection device over the Imraldi device, according to our results. After all, these injection devices’ structure and content are not the same, although both contain the same active ingredient, i.e. adalimumab. Our results highlight the importance of thorough information, not only with an information letter but also with the possibilities for individualized introduction in planning switching to biosimilars.